مشكلة تطبيق الشريعة الإسلامية في ولاية أتشيه بإندونيسيا : دراسة تحليلية - عارفين، عبد الغفور (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2010)
Aceh is the only province in Indonesia which has full authority to apply comprehensive Shari'āh law in its governance. This research aims to analytically study the problems that arise in implementing Shari'āh law in Aceh, which started almost nine years ago. The methodology used by the researcher include historical, inductive and analytical-descriptive approaches to provide the historical background of Aceh, its populations, the legal history of the implementation of Shari'āh law, and concept of Shari'āh law, in the province of Aceh. The researcher also discovers the problems that impede the application of Shari'ah law in the Province of Aceh and finds out the solutions to these problems. The most significant finding in this study is there are a lot of problems to be analyzed and solved in order to apply Shari' āh law in the province of Aceh while all Muslims have the responsibility for the success of this application in Aceh in particular and in the Islamic world in general. Muslims also have to be united and cooperate with each other to ensure the success of Shari'āh law implementation in all areas.